The MeatEater outdoor cookbook : wild game recipes for the grill, smoker, campstove, and campfire - Rinella, Steven; Ruane, Krista (Random House, 2024)
"In his previous books, outdoorsman and wild cuisine enthusiast Steven Rinella brought wild foods into the kitchen, teaching readers how to hunt, butcher, and cook wild fish and game to create gourmet dishes. Now, Rinella is bringing the kitchen into the wild in a cookbook that shows readers how to cook delectable meals in the peaceful solace of nature. Each chapter covers a different outdoor cooking method, such as grilling, smoking, and portable burner cooking, and each recipe indicates whether it's ideal for backyard cooking, car camping, or backpacking. The over 100 easy-to-follow recipes include: Stuffed Game Burgers 3 Ways Bulgogi Backstrap Lettuce Wraps Beaver Thigh Confit Grilled Lobster with Kelp Butter Bear Grease Biscuits Sweet Iron Pies As well as sharing these recipes, complete with mouthwatering photos, Rinella explains how to build an outdoor kitchen, build the perfect fire. With recipes ranging from simple to complex for outdoorists of all kinds, be they backyard grillmasters or backcountry big game hunters, The MeatEater Outdoor Cookbook is the essential companion for anyone who wants to eat well in the wild"--